The interpretation of Empedocles in the tradition of Middle- and Neoplatoism - Kohlschitter, Silke Angelika (Trinity College (Dublin, Ireland). Department of Classics, 1991)
The true interpretation of Empedocles provides an interesting problem in the history of thought. More or less universally, modern scholars assume that the cyclical presentation of the affairs of the world is intended literally by him, and this, indeed, seems to have been the interpretation of the first generation who interpreted Empedocles (Plato and Aristotle). In later Greek philosophy (i.e. from Plutarch onwards) however, a much more fascinating interpretation arose which disgarded the cosmic cycle and assumed it to be set out rather in the same way as Plato's followers thought of the Timaeus. This dissertation is thus really the exploration of this non-literal interpretation of Empedocles. I was provoked to carry out this examination by a recent work of Catherine Osborne, Rethinking Early Greek Philosophy, London 1987, which alerted scholars and redirected their attention to ancient secondary sources. I first survey the surviving Platonic, Middle Platonic and Neoplatonic testimonies and references about Empedocles with some preliminary notes on them. (I am not claiming that the material I present is complete. For the sake of the unity of the thesis it was necessary to confine myself to the testimonia that are relevant to the thesis and sufficient to illustrate what I want to say). Having seen how he is understood and adopted there, an account of the different levels of a non-literal interpretation of Empedocles is given. Finally, I provide a Neoplatonic interpretation of Empedocles. In two appendices, I discuss the Nachleben of Empedocles in the Jewish-Arabic tradition. It is suggested that the history of the interpretation of the Empedoclean cycle can be seen in parallel with the history of the interpretation of Plato's Timaeus. Three non-literal interpretations of Empedocles evolve from the testimonies examined: 1. Non-literal, cyclical interpretation: a Stoic type cycle is suggested -- 2. Non-literal, non-Neoplatonic interpretation; Empedocles' cycle is interpreted as an eternal state of physical affairs under the disguise of a cycle. 3. Platonic interpretation: Empedocles' σφαίρος is understood as the noetic world.
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin